﻿Studies of Diaporthe (Diaporthaceae, Diaporthales) species associated with plant cankers in Beijing, China, with three new species described - Yukun Bai; Lu Lin; Meng Pan; Xinlei Fan (MycoKeys, 2023)
The genus Diaporthe (Diaporthaceae, Diaporthales) comprises endophytes, pathogens and saprophytes, inhabiting a wide range of woody hosts and resulting in serious canker disease. To determine the diversity of Diaporthe species associated with canker disease of host plants in Beijing, China, a total of 35 representative strains were isolated from 18 host genera. Three novel species (D. changpingensis, D. diospyrina and D. ulmina) and four known species (D. corylicola, D. donglingensis, D. eres and D. rostrata) were identified, based on morphological comparison and phylogenetic analyses using partial ITS, cal, his3, tef1-α and tub2 loci. These results provide an understanding of the taxonomy of Diaporthe species associated with canker diseases in Beijing, China.